Pattern of Blood Products Consumption in a Teaching Hospital - Shrestha, Lava; Gurung, Numaya; Mahotra, Narayan Bahadur; Pradhan, Sait; Ghimire, Ananda; Pokhrel, Kailash Mani; Khanal, Kapil; Dhungana, Reechashree; Gautam, Naveen; Kandel, Sabita; Chaudhary, Sonam (Journal of Nepal Health Research Council, 2025)
Background: Blood transfusions are lifesaving, but resource limitations and inadequate utilization patterns pose challenges in low- and middle-income countries. In Nepal, detailed analyses of blood use practices, are needed to inform resource allocation and policy decisions. The objective of this study was to study the overall and component-specific use, explore temporal trends in utilization of blood and blood products. Methods: We conducted an observational study analyzing data from Blood Bank of Tribhuvan University Teaching Hospital (TUTH), a tertiary hospital (January 1st - December 31st, 2019). Data included patient demographics, blood groups, blood products requested and transfused, and facility type. Data analysis was conducted with SPSS v20.Results: Patients from TUTH had substantially higher blood product requests, requesting 25,716 units compared to only 1855 units across other centers combined. Blood groups A positive (8089, 31.4%) and and O positive (7851, 30.6%) were the most requested blood groups. Whole blood (11358, 44.2%) and packed red blood cells (9565, 37.2%) were most frequently requested. We observed monthly fluctuations in demand with peak of 2742 requests in December with a trough in June (1947 units). Notably, only approximately 46% of blood products requested from patients admitted to TUTH were ultimately transfused. Conclusions: Whole blood and packed red blood cells were the most frequently requested blood products. Eventhough whole blood was the most frequently requested blood product, the most transfused one was packed red cells. Peak demand was observed in December. Our study provides valuable insights into blood utilization patterns, underscoring the need for specific strategies to improve blood transfusion management practices. Keywords: Blood banking; blood transfusion; blood utilization; LMICs. Nepal.